PENGARUH LABA TUNAI, LABA AKUNTANSI, DAN EARNING PER SHARE (EPS), TERHADAP DIVIDEN KAS PADA KAS PADA SELURUH PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2018 - Ni Putu Budi Ariastuti; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2020)
Thej purpose ofj thisj study isj to examine thej effectj ofj cashj earningsj, accountingj earnings andj earnings perj sharej on cashj dividendsj.Thej population inj thisj study werej allj manufacturingj companiesj listedj on thej Indonesiaj Stockj Exchangej (IDX) ofj 154 companiesj. Research samplesj usingj purposive samplingj methodj, with a totalj sample ofj 129 samplesj. Thej analysisj technique usedj isj classicalj assumptions andj multiple linearj regression analysisj.Thej results showedj thej cashj profitj variable had a positive andj significant effectj on cashj dividendsj, which wasj indicatedj by thej cashj profitj variable value ofj 0.250 andj a significant value ofj 0j.002j. Thej results ofj thej accountingj profitj variabalj have a positive andj significant effectj on cashj dividendsj, which isj indicatedj by thej variable value ofj accountingj earnings ofj 0,337 andj a significance value ofj 0,000j. While earningj perj sharej hasj a negative butj significant effectj on cashj dividendsj shown inj beta) ofj -0j.335 andj significant atj 0,000j.